A Digital Feedback System to Support Implementation of Measurement-Based Care by School-Based Mental Health Clinicians. (29th March 2019) - Lyon, Aaron R.; Pullmann, Michael D.; Whitaker, Kelly; Ludwig, Kristy; Wasse, Jessica Knaster; McCauley, Elizabeth
Abstract : Evidence supports the utility of measurement-based care (MBC) to improve youth mental health outcomes, but clinicians rarely engage in MBC practices. Digital measurement feedback systems (MFS) may reflect a feasible strategy to support MBC adoption and sustainment. This pilot study was initiated to evaluate the impact of a MFS and brief consultation supports to facilitate MBC uptake and sustainment among mental health clinicians in the education sector, the most common mental health service delivery setting for youth. Following an initial training in MBC, 14 clinicians were randomized to either a digital MFS and brief consultation supports or control. Baseline ratings of MBC attitudes, skill, and use were collected. In addition, daily assessment ratings tracked 2 core MBC practices (i.e., assessment tool administration, provision of feedback) over a 6-month follow-up period. Clinicians in the MFS condition demonstrated rapid increases in both MBC practices, whereas the control group did not significantly change. For clinicians in the MFS group, consultation effects were significant for feedback and approached significance for administration. Over the follow-up period, average decreases in the current study were moderate with only 1 of the 2 outcome variables (administration) decreasing significantly. Inspection of individual clinician trajectories revealed substantial within-group trend variation. MFS may represent an effective MBC implementation strategy beyond initial training, although individual clinician response is variable. Identifying feasible and impactful implementation strategies is critical given the ability of MBC to support precision health care.